Determinants of Profitability in Indonesian Islamic Banking: Case Study in the COVID-19 Period - Wahyudi, Rofiul; Mutmainah, Lu’liyatul; Nahar, Faiza Husnayeni; Adha, Mufti Alam; Rifan, Akhmad Arif (Universitas Bangka Belitung, 2021)
With a high level of COVID-19 virus spread throughout the world, Indonesia is one of the countries in Southeast Asia affected by the largest transmission chain. This affects various layers of the industry in this country, one of which is financial institutions and the banking system. This paper tries to look at the performance of Islamic banking in the face of the COVID-19 pandemic. Using the linear regression method, the authors use ROA as the dependent variable. Whereas CAR, NPF, FDR, and BOPO as independent variables. The results show that CAR and BOPO have significant results while the rest do not show satisfactory results. It can be concluded that during the pandemic, Islamic banking experienced a pretty good and convincing performance.